Distribuce s lipoproteiny asociované fosfolipázy A2 v české populaci a její interakce s konvenčním kardiovaskulárním rizikem - Mayer, O; Seidlerová, J; Wohlfart, P; Trefil, L; Bruthans, J; Filipovský, J; Cífková, R (Vnitrni lekarstvi, 2013)
INTRODUCTION: Lipoprotein associated phospholipase A2 (Lp PLA2) represent new cardiovascular risk factor and potential treatment target. We aimed to analyze the epidemiological situation of this factor in Czech population. METHODS AND RESULTS: The study population consisted from 1 962 subjects, a random samples of general population (postMONICA study), and from patients with manifest coronary or cerebrovascular disease (Czech samples of EUROASPIRE III survey). Lp PLA2 activity was estimated using commercial kits by diaDexus Inc. in frozen samples. Increased activity (by definition, i.e. > 195 nmol/ min/ ml) was observed in 21.1 % of sample, no apparent difference between subject with and without manifest vascular disease was found. Males showed higher Lp PLA2 activity, than females (179.6 vs 146, resp., p < 0.0001), while no substantial increase with age was observed. Taking Lp PLA2 activity > 195 as dependent variable, following independent variables entered the multiple logistic regression: male gender [with odds ratio 4.26 (3.26- 5.58)], low HDL cholesterol (i.e. < 1.0 mmol/ l in males or < 1.2 mmol/ l in females) [3.49 (2.62- 4.64)], LDLcholesterol > 2.5 mmol/ l [6.95 (4.79- 10.07)] and lipid lowering treatment [0.59 (0.44- 0.79)]. In subject without manifest vascular disease, 6.3 % of them showed co incidence of markedly increased Lp PLA2 activity with high conventional risk (SCORE > 10 %). Expanding this group by intermediate risk subjects (ie. with Lp PLA2 activity 152- 194 and/ or SCORE 5- 9.9 %) leads to increase of this prevalence to 28.9 % of primary prevention subjects. CONCLUSION: Increased Lp PLA2 activity is in Czech population highly prevalent and with exception of lipid parameters, generally independent from conventional cardiovascular risk. However, up to 29 % of subject in primary prevention amalgamate increased Lp PLA2 activity with high conventional cardiovascular risk.
Keywords: 1-alkyl-2-acetylglycerofosfocholinesterasa; Female; rizikové faktory; Aged; kardiovaskulární nemoci; 1-Alkyl-2-acetylglycerophosphocholine Esterase; Humans; ženské pohlaví; Cardiovascular Diseases; mužské pohlaví; senioři; lidé; Male; lidé středního věku; Middle Aged; Risk Factors